America's Failing Experiment : How We the People Have Become the Problem - Goidel, Kirby., 1967- (Lanham Rowman & Littlefield, 2014)
Overview: America's Failing Experiment: How We the People Have Become the Problem, makes the controversial claim that the American political system suffers from too much democracy.
Include Notes and Index
Keywords: Political culture -- Political participation -- United States -- Democracy--Citizen participation